Analysis of epistemic practices in reports of higher education students groups in carrying out the inquiry-based activity of immunology - Manzoni de Almeida, Daniel; Marzin-Janvier, Patrícia; Frateschi Trivelato, Silvia Luzia (Investigações em Ensino de Ciências, 2016)
Practical classes in immunology are important to assist the learning of abstract theoretical concepts of biological phenomena learned in the classroom. Here, our proposal was the qualitative characterization of epistemic practices. Analysis of the results obtained from the investigative activities showed that student groups mobilize a huge variety of epistemic practices during reports writing, for example, to predict, conclude, name, describe, explain, opine, and the use of theoretical data for reviewing and evaluating the consistency of the data observed. A better understanding of these interactions can help in the teaching of Immunology classes for undergraduate students of life sciences and health courses.